2012
DOI: 10.1063/1.3689010
|View full text |Cite
|
Sign up to set email alerts
|

Electron emission mechanism during the nanosecond high-voltage pulsed discharge in pressurized air

Abstract: A comparison between the results of x-ray absorption spectroscopy of runaway electrons (RAEs) generated during nanosecond timescale high-voltage (HV) gas discharge and the simulated attenuation of the x-ray flux produced by the runaway electron spectrum calculated using particle-in-cell numerical modeling of such a type of discharge is presented. The particle-in-cell simulation considered the field and explosive emissions (EEs) of the electrons from the cathode. It is shown that the field emission is the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Wilson first proposed in 1924 that electrons might enter a state of continuous acceleration under a strong electric field [15]. Since then, many studies have reported the theory of electron runaway under a strong electric field [12, 16, 17], that is, the energy the electrons lose between collisions is less than the energy electrons accumulate from the strong electric field. The condition can be simplified as follows: normaldεnormaldx=eE(x)F(ε)>0 $\frac{\mathrm{d}\varepsilon }{\mathrm{d}x}=e\cdot E(x)-F(\varepsilon ) > 0$ where, e is the charge of the electron, E is the electric field where the electron is, x is the position of the electron, ε is the energy of the electron, and F ( ε ) is the effective friction force [18], that is, the energy loss function of the inelastic collision between electrons and gas molecules or atoms in the process of motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson first proposed in 1924 that electrons might enter a state of continuous acceleration under a strong electric field [15]. Since then, many studies have reported the theory of electron runaway under a strong electric field [12, 16, 17], that is, the energy the electrons lose between collisions is less than the energy electrons accumulate from the strong electric field. The condition can be simplified as follows: normaldεnormaldx=eE(x)F(ε)>0 $\frac{\mathrm{d}\varepsilon }{\mathrm{d}x}=e\cdot E(x)-F(\varepsilon ) > 0$ where, e is the charge of the electron, E is the electric field where the electron is, x is the position of the electron, ε is the energy of the electron, and F ( ε ) is the effective friction force [18], that is, the energy loss function of the inelastic collision between electrons and gas molecules or atoms in the process of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson first proposed in 1924 that electrons might enter a state of continuous acceleration under a strong electric field [15]. Since then, many studies have reported the theory of electron runaway under a strong electric field [12,16,17], that is, the energy the electrons lose between collisions is less than the energy electrons accumulate from the strong electric field. The condition can be simplified as follows:…”
Section: Introductionmentioning
confidence: 99%
“…It has a long history and it is widely used in the areas of high-energy electron beam generation, vacuum switching and illumination industry [2,3]. Recently, dynamical emission characteristics of gas-filled or vacuum diodes with cold cathode have been extensively investigated, especially in an inhomogeneous electric field provided by subnano-and nanosecond voltage pulses [4][5][6][7][8]. They are viable for the further studies aimed at generation of electron beams and x-ray radiation in air-filled diodes under high pressure [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies of the high-current subnanosecond discharge in gases, generation mechanisms of runaway electrons and accompanying X-rays, as well as the parameters of this plasma and the main applications of such discharges, were summarized in works [21][22][23][24]. The conditions and mechanisms of formation of homogeneous plasma aggregates with a high density and a large volume in strongly nonuniform electric fields of the high-pressure multielectrode corona discharge were considered in [25].…”
Section: Introductionmentioning
confidence: 99%